TI_GERICHTE 16.2015.11 vom 10. April 2017 , Azione di ripetizione per pagamento indebito - prova del pagamento indebito - TI Tribunale d'appello (2017)
Azione di ripetizione per pagamento indebito - prova del pagamento indebito